Assertive Communication in Health Care - Krstić, Ana; Kekuš, Divna (PONS - medicinski časopis, 2023)
In the middle of the last century, it was noticed that developed communication skills applied in the health practice holds great importance for establishing and maintaining healthy interpersonal relations, turning successful communication into a professional skill. Authors often point out that successful communication is considered one of the most important aspects of health professionals’ practice and a vital part of providing health care, as the foundation of human relations. According to the World Health Organization, quality communication is defined as one of the five skills necessary for a healthy and happy life, and therefore communication skills must be constantly refined and improved. Communication in health care is a complex, continuous and interactive process, which forms the basis for building positive relations between medical professionals and patients. As they communicate with a large number of people who are different in terms of education, culture, religion and social status, it is necessary for health professionals to master the skill of effective professional communication. Assertiveness is a communication style that represents a person’s ability to freely protect their own rights and confidently express their opinion, at the same time respecting and appreciating another person's opinion and showing empathy for their feelings. After determining the concept of assertiveness, the authors will also consider other communication styles, where assertiveness represents the middle point between passive and aggressive style. Obstacles or difficulties in the application of assertive behavior include: anxiety, excessive modesty, acceptance of other people's obligations, at the same time neglecting one's own needs, and being burdened by the "gender role", especially among women.
Keywords: assertiveness; assertive communication; communication styles; communication skills; health care